2021
DOI: 10.1111/maps.13717
|View full text |Cite
|
Sign up to set email alerts
|

Impact plume‐formed and protoplanetary disk high‐temperature components in CB and CH metal‐rich carbonaceous chondrites

Abstract: We report on the mineralogy, petrology, and oxygen isotopic compositions of ferroan olivine–pyroxene‐normative cryptocrystalline chondrules (Fe‐CCs) in CH chondrites and discuss their origin and the origin of other components in the genetically related CH and CB chondrites. There are two kinds of Fe‐CCs: (1) compositionally uniform (Fe/[Fe+Mg] = 0.17–0.34) chondrules with euhedral Fe, Ni‐metal grains and (2) metal‐free chemically zoned (Fe/[Fe+Mg] = 0.05–0.4) chondrules surrounded by ferroan olivine (Fa44−62) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 93 publications
(135 reference statements)
0
10
0
Order By: Relevance
“…It was suggested that CB plume material accreted together with "normal" chondritic material that predated the plume event and was probably present in the disk. Since CB and CH chondrites are genetically related, the presence of different aqueously altered chondritic lithic clasts, metamorphosed chondrules, heavily metamorphosed clasts, and fragments of an angrite-like asteroid observed in CH chondrites could be consistent with this late stage of disk evolution (Krot et al, 2021). Some of the "normal" chondritic components may have been heated conductively by the silicate vapor of the expanding plume and bow shocks (Stewart et al, 2019a(Stewart et al, , 2019b.…”
Section: Formation Of Sg 013 Lithologies and Their Componentsmentioning
confidence: 95%
See 4 more Smart Citations
“…It was suggested that CB plume material accreted together with "normal" chondritic material that predated the plume event and was probably present in the disk. Since CB and CH chondrites are genetically related, the presence of different aqueously altered chondritic lithic clasts, metamorphosed chondrules, heavily metamorphosed clasts, and fragments of an angrite-like asteroid observed in CH chondrites could be consistent with this late stage of disk evolution (Krot et al, 2021). Some of the "normal" chondritic components may have been heated conductively by the silicate vapor of the expanding plume and bow shocks (Stewart et al, 2019a(Stewart et al, , 2019b.…”
Section: Formation Of Sg 013 Lithologies and Their Componentsmentioning
confidence: 95%
“…Based on the apparent absence of interchondrule fine-grained matrix material in CB chondrites and their young age, Krot et al (2005) proposed that the CB plume event occurred after nearly complete dissipation of the accretionary disk, during the debris stage of its evolution (Krot et al, 2021). Subsequently, Meibom et al (2005) suggested that interchondrule and intermetal shock melts in CB chondrites may represent the remains of the missing matrix.…”
Section: Formation Of Sg 013 Lithologies and Their Componentsmentioning
confidence: 99%
See 3 more Smart Citations